Tazemetostat synergistically combats multidrug resistance by the unique triple inhibition of ABCB1, ABCC1, and ABCG2 efflux transporters in vitro and ex vivo - Budagaga, Youssif; Sabet, Ziba; Zhang, Yu; Novotná, Eva; Hanke, Ivo; Rozkoš, Tomáš; Hofman, Jakub (Biochemical pharmacology, 2023)
ATP-binding cassette (ABC) drug efflux transporters and drug metabolizing enzymes play crucial roles in pharmacokinetic drug-drug interactions and multidrug tumor resistance (MDR). Tazemetostat (EPZ-6438, Tazverik) is a novel epigenetic drug that has been recently approved for the therapy of advanced epithelioid sarcoma and follicular lymphoma. Additionally, this medication is currently being clinically tested to treat several other cancers such as non-small cell lung cancer (NSCLC). This study aimed to investigate the inhibitory effects of tazemetostat on selected ABC transporters/cytochrome P450 3A4 (CYP3A4) enzyme to comprehensively explore its role in MDR. First, our accumulation and molecular docking studies showed that tazemetostat is a unique triple inhibitor of ABCB1, ABCC1, and ABCG2 transporters. In contrast, tazemetostat exhibited only low level of interaction with the CYP3A4 isozyme. Drug combination assays confirmed that tazemetostat is a multipotent MDR modulator able to synergize with various conventional chemotherapeutics in vitro. Subsequent caspase activity assays and microscopic staining of apoptotic nuclei proved that the effective induction of apoptosis is behind the observed synergies. Notably, a potent MDR-modulatory capacity of tazemetostat was recorded in primary ex vivo NSCLC explants generated from patients' biopsies. On the contrary, its possible position of pharmacokinetic MDR's victim was excluded in comparative proliferation assays. Finally, tested drug has not been identified as an inducer of resistant phenotype in NSCLC cell lines. In conclusion, we demonstrated that tazemetostat is a unique multispecific chemosensitizer, which has strong potential to overcome limitations seen in the era of traditional MDR modulators.
Keywords: ABC transporter; Cytochrome P450; Drug-drug interaction; Non-small cell lung cancer; Multidrug resistance; Tazemetostat